Atrophic dermatofibrosarcoma protuberans: A pediatric case. - Ajaaouani, R.; Hali, F.; El Fatoiki, F.Z.; Mernissi, F.; Diouri, M.; Chiheb, S. (European Journal of Pediatric Dermatology, 2022)
DFSP is a rare mesenchymal neoplasm characterized by infiltrative growth. Atrophic DFSP is a rare variant of DFSP and 42 cases have been reported to date (6). Unlike classic DFSP, which typically manifests as a protruding neoformation, atrophic DFSP usually appears as a depressed, red to purplish-gray, rounded, ovoid, or irregularly shaped lesion. This aspect hardly leads to a clinical diagnosis of atrophic DFSP. On the other hand, physicians think of atrophic scar, idiopathic atrophoderma, localized scleroderma, lipoatrophy, atrophic dermatofibroma, and regressing panniculitis. Like classic DFSP, atrophic DFSP is predominantly seen in young adults. However, congenital and infantile cases have also been reported (5). In contrast to the classic DFSP, which has a slight male prevalence, atrophic DFSP shows a preference for females and the trunk is the most frequently affected site […].